The Influence of Trust and Knowledge Sharing on Employee Performance: A Study at Alfamart Minimarkets in East Telukjambe, Karawang, Indonesia - Wahyu, Priya Perdana; Raharso, Sri; Thahjawati, Sri Surjani (Manunggal Halim Jaya, 2025)
This study examines the effect of trust and knowledge sharing on employee performance at Alfamart minimarkets in Telukjambe Timur District, Karawang Regency. A quantitative research approach was used by distributing structured questionnaires to 182 respondents who had worked for at least six months. The collected data were analyzed using multiple linear regression. The results showed that trust and knowledge sharing have a positive and statistically significant effect on individual and collective employee performance. Trust contributes to a sense of psychological safety and fosters collaborative relationships among employees, while knowledge sharing facilitates information exchange and enhances individual competence. These findings underscore the strategic importance of cultivating a collaborative organizational culture that promotes collective learning, thereby contributing to improved performance and competitiveness in the modern retail sector. Furthermore, both variables collectively explain 78.1% of the variance in employee performance, indicating their substantial contribution to effective workforce outcomes.